2015
DOI: 10.1007/s00402-015-2287-6
|View full text |Cite
|
Sign up to set email alerts
|

Geometric analysis of an expandable reamer for treatment of avascular necrosis of the femoral head

Abstract: "Advanced core decompression" (ACD) is a treatment option for osteonecrosis of the femoral head (ONFH) that aims at complete removal of the necrotic tissue using a percutaneous expandable reamer and refilling of the head with an osteoconductive bone-graft substitute. The objective of this study was to evaluate if the success of ACD depends on the amount of necrotic tissue remaining after the procedure and how efficiently the necrotic tissue can be removed with the current reamer. Three-dimensional models of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Numerous studies have reported that the amount of the necrosis is an important factor affecting the efficacy of hip-saving surgery, and the larger the necrotic area, the higher the rate of surgical failure [ 13 19 ]. Landgraeber et al [ 20 ] reported that the amount of preoperative necrosis correlates significantly with treatment failure. Patients who were treated with advanced core decompression with a preoperative necrotic volume of less than 2500 mm3 have a relatively low failure rate of 13% in comparison to patients with a larger preoperative necrotic volume.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that the amount of the necrosis is an important factor affecting the efficacy of hip-saving surgery, and the larger the necrotic area, the higher the rate of surgical failure [ 13 19 ]. Landgraeber et al [ 20 ] reported that the amount of preoperative necrosis correlates significantly with treatment failure. Patients who were treated with advanced core decompression with a preoperative necrotic volume of less than 2500 mm3 have a relatively low failure rate of 13% in comparison to patients with a larger preoperative necrotic volume.…”
Section: Discussionmentioning
confidence: 99%
“…Core decompression combined with bone grafting (with or without adjuvants) as a joint-preserving surgical treatment has been widely recognized before [3,16,26,27,28] . In recent years, studies also showed that patients with ARCO classification system stage II treated by Core decompression combined with autologous bone and BMA had good outcomes [2Other studies have already shown the usefulness of eliminating the necrotic bone and structural support by the adjuvant substances in the treatment of early ANFH ies [3,22,30] . Arlet and Ficat first introduced core decompression in 1964 and they reported "good to very good results" in 90% of these hips on clinical evaluation and in 79% on radiographic evaluation [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Won Seok et al reported similar results: the survival rates of small necrotic lesions (100%) and medium-sized lesions (84.1%) were significantly higher than those of large necrotic lesions (53.8%) [ 6 ]. Stefan et al reported that no treatment failure was observed in patients with remaining necrosis of less than 1000 mm 3 at a mean follow-up of 33 months [ 35 ]. One reason for this association may be intuitive as patients with larger necrotic lesion in subchondral lesions may have less mechanical support of the femoral head and a higher risk of hip collapse.…”
Section: Discussionmentioning
confidence: 99%